Belajar Mandiri dan Pembelajaran Berbasis Daring di Perguruan Tinggi - Muhammad Tahir; M Darwis (JOURNAL OF EDUCATIONAL TECHNOLOGY, CURRICULUM, LEARNING AND COMMUNICATION, 2021)
This study aims to determine the independence of students in conducting off-campus learning activities without the physical presence of faculty but using information technology tools in different rooms and locations. The variables for independent learning and online-based learning were limited during the coronavirus pandemic (COVID-19). The secondary data needed comes from student responses to online-based learning that are linked to aspects of independent learning activities for students. The population in this study was all undergraduate students in Educational Technology, Universitas Pejuang RI. Macassar. The sample was collected using a dedicated sampling method that focused only on students enrolled in the Education Communication System course. Due to the COVID-19 pandemic, online-based learning was implemented. The data was collected through online questionnaires and in-depth interviews with several students in order to obtain more detailed information. The data analysis technique used in this study is percentage description analysis, which consists of data acquisition, data reduction, data presentation and final drawing. The results of this study show that the activities of students in online-based learning in the subject of educational communication systems show a positive correlation with learning independence, with details of the aspects being assessed. The ability to ask and answer questions about the material being taught is (61.12%) and can provide immediate feedback on the faculty of the instructor's questions (60.14%) on the aspect of the ability to do tasks appropriately and the content of the Material processed with references gives solid and integrated course material (50.22%). The conclusion is behind online learning and its problems. However, positive data are obtained from the independent attitude of students to learning. This is because online learning in college can improve the ability to ask questions on the fly, provide feedback according to the originality of their thoughts, and process course materials with other supportive materials of the initiative. alone. Keywords: Independent learning; online learning